Faktor – Faktor Yang Mempengaruhi Kejadian Anemia Pada Ibu Hamil di Puskesmas Juwiring - Wahyuni, Sri; Hartati, Lilik; Dynamurti Wintoro, Piscolia (INVOLUSI: Jurnal Ilmu Kebidanan, 2025)
Data on anemia cases in Central Java Province is 57.1% and anemia is mostly found in TM III pregnant women. Meanwhile, the prevalence of anemia in pregnant women in Klaten Regency is 9.19% [1]. Anemia in pregnancy is a national problem because it reflects the socio-economic welfare of society, and also has a huge influence on the quality of human resources. Pregnancy anemia is called "potential danger to mother and child", which is why anemia requires serious attention from all parties involved in health services at the front line. Anemia is considered a risk factor and can result in life-threatening complications for the mother and fetus [2]. This study aims to determine the factors that influence the incidence of anemia in pregnant women. The research method used uses a qualitative research design with a cross-sectional approach. The population in this study were all 86 pregnant women who experienced anemia at the Juwiring Klaten Community Health Center. The data source was taken from January - December 2023, the research instrument used was the medical record data source. Data analysis used the chi-square test followed by logistic regression testing. The results of the study showed that anemia most often occurred in maternal age not at risk (73.3%), parity not at risk (86.0%), status without KEK (68.6%) and upper/higher education level (75.6% ). Factors associated with anemia in pregnant women are maternal age (p-value; 0.035: OR; 2.489), parity (p-value; 0.031; OR; 4.486) and CED status (p-value; 0.011; OR; 2.822). CED status is a factor that influences the incidence of anemia in pregnant women. Early detection and prevention of anemia needs to be improved during ANC visits.